Aplicativos digitais e ensino-aprendizagem de espanhol/le: um estudo com alunos do Instituto Federal do Maranhão. - SILVA, Elizabeth Corrêa da (2019)
Considering that reading and writing activities are not limited to a linguistic and cognitive action, but they also consist in a way of being in the world and acting on it, it is imperative that students are able to interact with texts in other languages, mobilizing resources that ensure the construction of meanings in different sorts and supports, and also in integrations of varied formats, also present in the digital medium. Therefore, the guiding question for the development of this research was the investigation of what results could be obtained from the articulations between printed and digital didactic material in Spanish language classes. In this sense, our general objective in this research consisted in analyzing potentialities in the articulation between printed courseware and digital applications Edpuzzle, Padlet and Quizizz in the teaching-learning process of Spanish as a foreign language, of a Federal school system in the city of São Luís / MA. The research covered the convergence of the theoretical framework on Education, Digital Technologies and Language Teaching. We have, therefore, as theoretical support authors such as Pozo (2004); Bottentuit Junior (2010, 2017); Santaella (2005, 2013); Leffa (2008); Coscarelli (2005, 2016); Ribeiro (2016, 2018), Rojo (2012, 2015) and others. Therefore, it is a case study, exploratory and descriptive, with practical implementation and qualitative analysis approach. For that, the participant observation is used as instruments and techniques for data collection; the application of questionnaires, with open and closed questions; and a focus group interview with the students who collaborated with this study. We describe and analyze activities that use digital applications (Edpuzzle, Padlet and Quizizz) articulated to work with the printed courseware, developed with twenty-seven Spanish-speaking students, within November and December of 2018. The obtained results indicate that there is space for treatment and use of digital technologies based on some of the experiences pointed out by the students in the Spanish language classes, as well as in the teaching plan of the subject and in the approach to the didactic book adopted in the Institution. The evaluation of students concentrated predominantly on a positive dimension around the set of applications used. Since this study involved the task of searching and selecting information, we understand that prior work with students about the perspective of digital citizenship, especially on questions of information search, reliability of sources and ethics in an online environment, would be important. Besides that, even though applications such as Padlet potentialize collaborative work, it is necessary to think strategies so that activities can be developed, in fact, with this inclination. In relation to the activity with Quizizz, we verified that the elements of games can be important resources to motivate the students' engagement and motivation. We believe that it is important to think, together with the use of the application, other interventions that allow us to explore issues of discursive content or that require greater reflection of the student without the pressure of a given time. We suggest, for future research on this topic, the work with the applications used from the Mobile Learning approach; in the teaching-learning process of Spanish in an online environment; and research into other digital applications that explore working with oral production skills.